Sistem Informasi Manajemen Untuk Media Sosial Sebagai Digital Marketing - Citra Anisa Putri; Muhammad Fajar Nursandi; Velintinus Riyan Tamba; Cahyati Komalasari; Sri Ayu Rahmawati (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
In the digital era, social media has become one of the most effective and affordable marketing tools for various types of businesses. To manage marketing activities in a more structured and data-based manner, the integration between social media and Management Information Systems (MIS) is becoming increasingly relevant. This study aims to examine the use of MIS as a social marketing media and how its application can improve promotion efficiency and decision-making quality. Using a literature study method, this study collects and analyzes various scientific references that discuss the role of MIS in the world of digital marketing. The results of the study show that MIS can help companies manage customer data, monitor campaign performance, and adjust marketing strategies in real time. Case examples from MSMEs and local companies strengthen the evidence that the integration of MIS and social media can increase the effectiveness of promotions and adaptation to market changes. Therefore, the use of MIS in a digital marketing strategy is a strategic step to increase competitiveness and sustainable business growth.